2015
DOI: 10.1159/000367746
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Hepatic Arterial Infusion Chemotherapy

Abstract: Background: Hepatic arterial infusion chemotherapy (HAIC) is frequently used to treat advanced hepatocellular carcinoma (HCC) in Asian countries. However, there is a lack of evidence supporting the use of HAIC. Summary: Many studies report high response rates in patients with advanced HCC receiving HAIC, and clinical responses translate to survival benefits. Therefore, prediction of an antitumor response is important in selecting appropriate treatments. There are no proven post-sorafenib therapeutic measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 47 publications
2
81
0
Order By: Relevance
“…However, in previous combination studies with TACE, the median OS ranged from 18 months (shortest) to 32 months (longest) ( Table 1 ), suggesting that the duration of the study needs to be extremely long when evaluating OS as a primary endpoint. In clinical studies that are terminated early because of tumor progression or adverse effects, patients often receive various post-trial treatments, such as hepatic artery infusion chemotherapy [20][21][22] , ablation [23][24][25] , or systemic therapy [26][27][28][29] . In such cases, post-trial treatment likely affects OS, making it difficult to evaluate treatment outcomes using OS, especially in studies of TACE in patients with intermediate-stage HCC.…”
Section: Proposal Of a New Primary Endpoint In Tace Combination Trialsmentioning
confidence: 99%
“…However, in previous combination studies with TACE, the median OS ranged from 18 months (shortest) to 32 months (longest) ( Table 1 ), suggesting that the duration of the study needs to be extremely long when evaluating OS as a primary endpoint. In clinical studies that are terminated early because of tumor progression or adverse effects, patients often receive various post-trial treatments, such as hepatic artery infusion chemotherapy [20][21][22] , ablation [23][24][25] , or systemic therapy [26][27][28][29] . In such cases, post-trial treatment likely affects OS, making it difficult to evaluate treatment outcomes using OS, especially in studies of TACE in patients with intermediate-stage HCC.…”
Section: Proposal Of a New Primary Endpoint In Tace Combination Trialsmentioning
confidence: 99%
“…According to this algorithm, sorafenib is indicated for patients diagnosed with Child-Pugh class A HCC with extrahepatic spread or vascular invasion. Sorafenib is also recommended for patients with Child-Pugh class A HCC where transcatheter arterial chemoembolization (TACE) [7][8][9][10][11] and hepatic arterial infusion chemotherapy [12,13] are not indicated. In the present study, we examined the efficacy of sorafenib treatment and the clinical outcome in 314 patients at 5 general hospitals in Kagawa Prefecture, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…These reports suggested that surgical resection could be the best option for HCC patients with BCLC stage B disease. Furthermore, in some patients, TACE resistance due to the repeated TACE procedure should end up in the selection of other treatment strategies, including sorafenib and hepatic arterial infusion chemotherapy (HAIC) [15,16,17,18,19,20,21]. Although TACE is the most frequently selected treatment for the patients in BCLC stage B, other treatment options should be applied depending on the condition of individual patients in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%